Introdução da programação linear no ensino médio por meio da resolução de problemas - SILVA, Leandro Carvalho da (Universidade Federal do Tocantins, 2023)
Linear Programming is a tool strongly used in solving problems in different segments since it aims to optimize a function. This work aims to expose some applications that can be worked on during High School, using Linear Programming, as it is a mathematical tool with a practical and contextualized character. For the development of this work, a bibliographic study about Linear Programming and its applications in High School was carried out, given the great possibility of correlating several mathematical contents provided for in the National Common Curricular Base for this stage of teaching. Due to the fact that Linear Programming is part of one of the branches of Operational Research, during the development of the present work, the purpose and context in which Operational Research arose will be presented, as well as two methods of solving optimization problems using to Linear Programming; the Graphic Method and the Simplex Method. The work also motivates the use of technology in the classroom by suggesting the use of the application Linear Program Solver, for solving more complex problems involving Linear Programming